The Dialectics Between Constitutional Identity and Common Constitutional Traditions: Which Language for Cooperative Constitutionalism in Europe?. Issue 8 (December 2019) - Fichera, Massimo; Pollicino, Oreste
Abstract: This Article revisits the role and function of constitutional identity and common constitutional traditions and claims that the latter have had an increasingly stronger influence on the process of European integration—more than may appear at first sight. In addition, the relevance of common constitutional traditions has not been undermined but, on the contrary, strengthened by the emergence of fundamental rights in EU law and the subsequent conferral of binding force on the Charter of Fundamental Rights. Constitutional identity and common constitutional traditions are part of two discourses—security and fundamental rights—which are an expression of the security of the European project as an overarching frame characterizing the EU as a polity and legal system. After an overview of some of the most important rulings of the Court of Justice of the European Union, this Article concludes by emphasizing the importance of the recent conciliatory attitude recently adopted by the Court of Justice, although the more ambivalent attitude of the Italian Constitutional Court indicates how conflictual features are becoming increasingly important and can no longer be concealed as the EU reaches a more advanced stage of integration.